Peningkatan Pengetahuan Komprehensif tentang Menopause di Posyandu Lansia - Is Susiloningtyas; Friska Realita; Meilia Rahmawati (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
The number of elderly people in the world, including in Indonesia, is increasing every year. Estimated increase from 2000 to 2050 will double from about 11% to 22%, or in absolute terms increase from 605 million to 2 billion elderly (Ministry of Health, 2013). This increase is influenced by education, the environment and a healthy lifestyle. Healthy lifestyles in the elderly such as getting used to doing physical activities, consuming foods with balanced nutrition, not smoking and not consuming alcohol (Kemenkes, 2013). The Ministry of Health's efforts in an effort to improve the health status of the elderly, carry out several programs, including increasing counseling and disseminating health information, especially about hypertension where hypertension mostly attacks people aged > 40 years. The problems that occur are that most of the elderly do not really know good nutrition for the elderly, the awareness to come to the posyandu for the elderly and do a physical examination. This problem can be overcome by maintaining a healthy lifestyle and diet. The method used in this community service activity is through counseling activities and physical examinations for the elderly group at the Posyandu for the elderly. 25 and less than 20%.